Enteric Dissolution Enhancement of Engineered Gastro Resistant Omeprazole Tablets using Hydroxypropyl Methylcellulose Acetate Succinate - Mohapatra, Sagar Kumar; Sahoo, Rudra Narayan; Mallick, Subrata; Mohapatra, Rajaram (Indian Journal of Pharmaceutical Education and Research, 2021)
Purpose: Oral drug delivery system has always been a preferred choice for the treatment of peptic ulcer and gastroesophageal reflux diseases. Being a proton pump inhibitor omeprazole restricts gastric acid secretion but the foremost downside is its degradation in acidic environments. The systemic absorption of gastro-unstable drugs can be improved by the enteric coating. Materials and Methods: This study was aimed at developing an effective enteric coating for omeprazole tablets using HPMC E5-LV and Hydroxypropyl Methylcellulose Acetate Succinate (HPMC-AS) polymers. The core tablets were subcoated with HPMC E5-LV which acted as a barrier between core tablet and enteric coated tablet. The enteric coating was applied using HPMC-AS. Results: Dissolution information unveiled that the enteric coat remained in place for 2 hr in acidic medium (0.1N HCl) and later dissolved when came in contact with basic media (acetate buffer pH 6.8), it dissolved within a jiffy. Conclusion: The release profile showed 91 to 98% drug release within 1hr in pH 6.8 Acetate buffer. Further instrumental analysis was performed to ascertain drug-polymer interaction.
Keywords: Proton pump inhibitor; Enteric coating; HPMC; Omeprazole; Dissolution enhancement